1983
DOI: 10.1063/1.444793
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of nematic mixtures. I. Polar–polar and nonpolar–nonpolar systems

Abstract: The thermodynamic stability, the dielectric, diamagnetic, and elastic properties of mixtures of polar as well as those of nonpolar nematic liquid crystals were investigated and compared to the properties of their components. Small deviations from the ideal behavior were observed and attributed to differences in the packing of unlike molecules which mainly depend on steric factors. Clearing points obtained by the extrapolation method are shown to appreciably deviate from the actual values.(3) 906

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Binary mixtures derived from mixing of two pure mesogens closely resembling in their molecular structure and geometry (conformation) are known to stabilize thermodynamically stable LC phases of the constituent compounds . For example, it has been observed that a binary mixture made from two nematogens with nearly identical chemical structures and geometries show an enantiotropic nematic phase . These observations prompted us to select two mesogens exhibiting the SmA b phase.…”
Section: Resultsmentioning
confidence: 99%
“…Binary mixtures derived from mixing of two pure mesogens closely resembling in their molecular structure and geometry (conformation) are known to stabilize thermodynamically stable LC phases of the constituent compounds . For example, it has been observed that a binary mixture made from two nematogens with nearly identical chemical structures and geometries show an enantiotropic nematic phase . These observations prompted us to select two mesogens exhibiting the SmA b phase.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the dielectric, diamagnetic, viscous, and elastic constants, as well as the nematicisotropic transitions of solutions of homologues, approximately obey the additive rule [280]. This fact is employed for the comparison of physicochemical and electro-optical properties of the pyrimidin-2,5-diyl and reference derivatives (mixtures 5-4-5-6, Tables 5, 6).…”
Section: Comparative Characteristics Of Liquid Crystalsmentioning
confidence: 99%
“…Beside of the high extent of molecular chirality of a CC, another factor affecting the HTP values in N* systems is usually considered to be elastic constants, in particular, the twist elastic constant, K 22 , of selected nematic [3,31,32]. The nematic III has less strong elastic properties in comparison with 5CB (K 22 is about 2.8610 212 N for some derivatives of oxyphenylbenzoate [33] and 3.2-3.4610 212 N for 5CB [34][35][36]) and could be expected to be twisted more effectively. However, this was not revealed in the case of CCs 1.…”
Section: Mesomorphic Properties Of Ccs 1-3mentioning
confidence: 99%